Relationships between ultrasonic, immunological changes in the progression of liver steatosis and fibrosis in patients with chronic diffusive liver diseases of various etiologies - Yu. M. Stepanov; V. I. Didenko; I. S. Konenko; O. M. Tatarchuk (Zaporozhye State Medical University, 2019)
Objective. To determine the relationships between ultrasound and immunological changes in the progression of steatosis and liver fibrosis in patients with chronic diffuse liver diseases (CLD) of various etiologies. Materials and methods. We examined 120 patients with CLD. Patients were distributed according to the etiological factor of the development of steatosis and liver fibrosis: Group I - 24 patients with non-alcoholic fatty liver disease (NAFLD), ІІ - 37 patients with non-alcoholic steatohepatitis (NASH); Group III - 21 people with chronic viral hepatitis associated with the C virus (HCV). Group IV consisted of 18 patients with alcoholic liver disease (ALD), group V - 20 patients with toxic hepatitis (TG). Sonographic abdominal examination, ultrasound attenuation coefficient (UAC) and shear wave elastography (SWE) of the liver / spleen were performed. The content of cellular immunity parameters, the level of interleukin (IL)-6, IL-10, tumor necrosis factor alpha (TNF-α), insulin and HOMA-IR were determined. A correlation analysis was made between ultrasound and immunological parameters in the examined patients. Results. In patients with CLD, changes in liver structure in the form of heterogenety were detected in 97 (80.8 %) (P < 0.001). The maximum values of SWE of the liver were observed in patients with ALD (18.10 ± 2.68) kPa, minimal - with NAFLD. The stiffness of the spleen was highest in patients with ALD 24.09 ± 3.68 kPa. TNF-α was significantly higher than the control values with NASH by 11.6 times (P < 0.05), HCV by 13.9 times (P < 0.05), ALD by 9.4 times (P < 0.05) and TG by 9.5 times (P < 0.05). The concentration of IL-6 was 2.1 times higher (P < 0.05) in patients with NASH and CHC, 2.5 times higher (P < 0.05) in patients with TG. The TNF-α / IL-10 ratio was increased by 7.1 times (P < 0.05) in patients with NAFLD, by 19.3 times (P < 0.05) in patients with NASH, by 14.4 times (P < 0.05) in patients with chronic hepatitis C, by 14.0 times (P < 0.05) in patients with ALD and by 8.4 times (P < 0.05) in patients with TG. When conducting a correlation analysis, it was revealed that in patients with NAFLD, the level of TNF-α had a positive relationship with the spleen stiffness (r = +0.601, P < 0.01). In patients with HCV, the level of IL-6 was associated with spleen stiffness (r = +0.680, P < 0.05), liver stiffness (r = +0.618, P < 0.05) and the degree of fibrosis (according to METAVIR) (r = +0.573, P < 0.01). In patients with ALD, an increase in liver stiffness is accompanied by a significant increase in the NOMA index (r= +0.843). In patients with TG, a negative relationship was found between the level of T-helper cells and stiffness of spleen (r = - 0.577, P < 0.05) and liver (r = -0.522, P < 0.05). Conclusion. The progression of liver steatosis is accompanied by a lack of cellular immunity and an increase in the level of pro-inflammatory cytokines. An increase in structural changes of the liver and spleen, as well as the increase in the degree of steatosis, is accompanied by activation of pro-inflammatory cytokines, depletion of the anti-inflammatory response and increased insulin resistance.